Older persons’ perceptions about advanced directives and end of life issues in a geriatric care setting in southwestern Nigeria (2019)
Introduction: advanced directives enable the planning of care and support services independent of the older person’s ability to make the decision. There is a paucity of information regarding the views and preferences regarding advanced directives and other end of life issues among older persons in low and middle-income countries such as Nigeria. The study aimed to explore the knowledge, attitude and belief of older persons regarding decision making surrounding end of life and advance directives. Methods: data were collected through focus group discussions at a monthly social gathering of outpatients in a geriatric center in Oyo State, Nigeria. Discussions were audiotaped, transcribed and analyzed manually using a thematic approach. Results: respondents’ knowledge about the end of life care and advanced directives as prescribed in high income settings were sparse and did not include choices about treatment options or any medical directives. The predominant perceptions among the participants bordered mainly on the arrangements for place of death, burial and property sharing. Participants listed in order of preference the major decision makers in the advanced directive process mainly, the oldest male child, religious leaders and legal practitioners. Conclusion: our findings imply the need for improving knowledge and awareness about the benefits of advanced directives among older persons with a focus on opportunities for their active participation